Effect of Discipline, Work Stress And Compensation on Employee Performance at PT. Central Proteina Prima, TBK: Effect of Discipline, Work Stress And Compensation on Employee Performance at PT. Central Proteina Prima, TBK - Holfian Daulat Tambun Saribu; Damari Zenaro; Metze Sylviany; Ferio Jordanio (Institute of Computer Science (IOCS), 2020)
Research at PT Central Proteinaprima, Tbk, aims to examine the effect of work discipline, job stress and job compensation to the decline in the performance of employees. The data used are primary data collected from the questionnaire. The population is karyawanPT Central Proteinaprima, Tbk, andsampling techniques using simple random sampling.The analysis model is a model of multiple linear regression analysis, the coefficient of determination simultaneous testing (Test-F) and partial (t-test). The results showed the discipline of work, job stress and job compensation simultaneously significant effect on employee performance. Partially labor discipline and labor compensation significant effect on performance while job stress had no significant effect on employee performance.